Folk groups and folklore genres : a reader - Oring, Elliott, 1945- (Utah State University Press, 1989)
Compiled to accompany the best-selling textbook, Folk Groups and Folklore Genres: An Introduction, the selections in this anthology extend the discussion in diverse directions, alert the reader to new problems, and introduce alternative perspectives. The essays include folklore classics and recent works, and are organized in sections that correspond to the chapter headings in An Introduction.